Естетика сучасної української народної балади: перспективи дослідження - Козловський, В. (Матеріали до української етнології, 2007)
The article presents one of the ways of researching the aesthetics of the folk ballad. Artistic and poetic peculiarities of the genre are considered in the light of the categories of the dramatic, tragic, and heroic.